The efficacy of a single maintained contact drop piece manipulation technique in the treatment of sacroiliac syndrome - Botha, Quentin Martin (2008)
Thesis (M.Tech.: Chiropractic)- Dept of Chiropractic, Durban Institute of Technology, 2005. xiii, 129 leaves :|bill. (some col.) ;|c30 cm === Research indicates the sacroiliac joint (prevalence of sacroiliac syndrome ranges from 19.3% and 47.9% (Toussaint et al., 1999)) as being the primary source of low-back pain in 22.5% of patients with back pain (Bernard et al., 1987:2107-2130).